Accelerating Solar Power Generation to Achieve India's Net-Zero Goals: A Factor-Based Study - Akilesh, A; Damodaran, K (International Journal of Sustainable Energy Planning and Management, 2025)
The commitment of India towards net-zero emissions, as announced at COP26, has led to remarkable transformations in its power sector. Despite being rich in diverse energy resources, India holds substantial potential for solar power generation, which is believed to play a crucial role in its journey toward net-zero emissions. Even though some states of India have achieved great milestones in the solar energy generation, still the progress seems insufficient and there exist regional imbalances. This shortage and imbalance may be attributed to various factors including fiscal, geographical and political elements. From the panel data analysis to identify the most influencing factors of solar power generation across 15 states, the cost of solar modules and the land availability were found to be the major drivers. Hence, through further investigation, the study suggests altering the existing scheme, especially PM Surya Ghar Muft Bijli Yojana to ensure real monetary benefits for individuals through rooftop solar systems; progressive subsidy rates; zero-tax for solar modules; and introduction of district-level green land banks tailored for solar energy projects.